Factores criminológicos que inciden en la perpetración del delito de extorsión - Ortega Huerta, María Yesenia (2025)
In this research work it has been possible to show how the crime of extortion has reached significant figures throughout Ecuador and especially in the canton Cañar from the year 2023, due to the increase in crime, insecurity and organized crime, It can be identified that the main motive used by criminals in this jurisdiction is the extortive vaccine, which consists of threats, threats of violence, injuries, against the life and integrity of the victims through calls, messages or any other means to obtain economic and patrimonial benefits. Thus, this crime is currently typified and punished in article 185 of the COIP, whose prison sentences range from three to ten years depending on the characteristics of the facts perpetrated. Therefore, it is clear that the general objective of the research has been met, which is to determine the main criminological factors that influence the perpetration of the crime of extortion, which has been addressed through a qualitative research approach, in order to conclude that there is still much more to do to achieve the eradication of this social phenomenon that causes serious harm to victims not only economically, Therefore, the State has the obligation to toughen and strengthen the criminal law that regulates this type of crime, which must be accompanied by institutional and social support through plans, policies and strategies aimed at the prevention, punishment and eradication of extortion.